Organizational justice and organizational commitment relationship: A research on 4 and 5 star hotel employees in Istanbul - Uysal, Levent; Akgün, Serkan (Yüksekbilgili Eğitim ve Danışmanlık Ltd. Şti., 2021)
The purpose of this research is to examine the relationship between organizational justice and organizational commitment in four- and five-star hotel businesses operating in Istanbul. It is possible to define organizational justice as “a concept that includes how fair and moral practices and transactions are perceived within the organization and how the organization is affected as a result of these perceptions”. Organizational commitment is the bond that a person establishes between the institution he / she works for and on various grounds. To date, organizational justice and organizational commitment have been regarded as two interrelated concepts theoretically. In this study, the relationship between organizational justice and organizational commitment was tried to be examined through a two-scale questionnaire applied to 426 participants. The collected data were analyzed in SPSS 22 program and hypotheses were tested. As a result of the analyzes, organizational justice and organizational commitment differed across demographic variables; and it seems that they have a positive meaningful relationship among themselves.
Örgütsel adalet ve örgütsel bağlılık ilişkisi: İstanbul’da 4 ve 5 yıldızlı otel çalışanları üzerine bir araştırma
Keywords: Organizational Justice; Organizational Commitment; 4 and 5 Star Hotel Employees; Örgütsel Adalet; Örgütsel Bağlılık; Otelcilik Sektörü; 4 ve 5 yıldız otel çalışan